Molecular structure and morphology of self-assembled microspheres in a fluorene-based conjugated copolymer by X-ray diffraction and scattering - Agnolin, Érick Henrique (2025)
Conjugated polymers lead in modern optoelectronic technology with a wide range of applications, most notoriously as organic light-emitting diodes, organic field-effective transistors, capacitors, organic solar cells, and sensors. In this work we present a molecular and morphological study of the photoluminescent, blue-light-emitting poly[9,9-bis(3-(tert-butyl- propanoate))]fluorene-co-9,9-dioctylfluorene) (pFeF8) conjugated copolymer based on fluorene and studied by Wide-Angle X-ray Diffraction (WAXD) and Small-Angle X-ray Scattering (SAXS). Complimentary multi-technique analysis is employed with Solid-state Nuclear Magnetic Resonance (13 C NMR), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), and Density Functional Theory (DFT). The 13C NMR spectrum of expected signals validated the molecular structure, indicating the presence of carbonyl, aromatic, and aliphatic carbons in the polymer. Thermodynamic transition temperatures are highlighted by DSC, displaying high thermal stability and temperature thresholds for glass-transition temperature Tg = 150 ºC, softening temperature Ts = 220 ºC, and TGA shows double-stage decomposition at Td > 250 and > 400 ºC. SAXS analysis revealed the self-assembly nature of highly polydisperse isotropic microspheres with a well-defined D(r) histogram. WAXD analysis identified broad diffraction peaks at 2θ ≈ 19° and 2θ ≈ 6°, correlating with π-stacking distances and d-spacing attributed to aliphatic side groups, respectively. Lattice parameters of a = 14.7 Å, b = 4.7 Å, and c = 18.5 Å are proposed for the precipitate. Upon recrystallization, the superimposed reflection at 2 ≈ 19° gives rise to multiple reflection peaks at 2θ values of 6, 18, 20, 21.5, and 23.8 degrees associated with d-distances varying as a function of stacking between adjacent polymer chains.